DEVELOPMENT OF WORDWALL WEBSITE MEDIA FOR TEACHING VOCABULARY - Gantari, Anissa; Saifudin, Ahmad; Mubarok, Tyas Alhim (Journal of English Education and Linguistics, 2024)
The use of learning media will facilitate teachers and students in the English learning process. One of the learning media that can be used is Wordwall. This research aims to develop materials using learning media based on the Wordwall Website and analyze the development results related to its suitability for vocabulary teaching. The subjects of this study were students of grade 10-2 at Madrasah Aliyah Sirojut Tholibin. The research employed the Research and Development (R&D) method. The development model used in this research was ADDIE which consists of five steps: Analysis, Design, Development, Implementation, and Evaluation. In the development process, there was the involvement of instrument experts, product experts, and material experts before the media was tested on students. Each result provided by the expert was used as material for improvement. The validation results from instrument experts amounted to 80%, product experts 90%, and material experts 78%. It means that the learning media developed is "valid" to be tested on students as learning media. After the trial process, students gave responses with an average percentage of 84.3%. It means that the media is also "valid" to be used to help improve their vocabulary and learning motivation in English lessons.